Serum Iron Status, Total Iron Binding Capacity, and Ferritin in Preeclampsia: A Cross Sectional Comparative Study from Northern India - Sidhi Parmar; Dr. Chitra Upadhyay; Dr. Rekha Bagla; Ms. Jaya Sharma, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Dysregulated iron metabolism and oxidative stress are implicated in the pathogenesis of pre eclampsia (PE), yet evidence from South Asian populations remains limited. Objective: To compare serum iron, total iron binding capacity (TIBC) and ferritin concentrations between women with PE and normotensive pregnant controls receiving routine antenatal iron prophylaxis. Methods: In a hospital based cross sectional study at a tertiary centre (September 2023 – August 2024), 64 singleton pregnancies ≥ 20 weeks’ gestation were enrolled (32 PE; 32 controls). PE was defined as blood pressure ≥ 140/90 mmHg plus proteinuria ≥ 1+ on dipstick. Venous blood was analysed for serum iron (ferrozine method), TIBC (saturating–precipitating assay) and ferritin (two site chemiluminescent immunoassay). Between group comparisons used Student’s t test; significance p < 0.05. Results: Mean gestational age was lower in the PE group (36.2 ± 1.1 weeks) than controls (37.9 ± 1.2 weeks; p < 0.001). Serum iron was significantly higher in PE (126.4 ± 39.5 µg/dL) versus controls (83.9 ± 25.5 µg/dL; p < 0.001), while TIBC was lower (354.6 ± 52.6 vs 417.0 ± 59.2 µg/dL; p < 0.001). Ferritin was more than doubled in PE (88.0 ± 37.8 vs 38.6 ± 26.4 ng/mL; p < 0.001). Conclusions: In iron supplemented pregnancies, PE is associated with raised circulating iron and ferritin together with reduced TIBC, supporting a role for iron mediated oxidative stress in its pathophysiology. Routine indiscriminate antenatal iron supplementation may warrant re evaluation, and iron indices may serve as inexpensive early markers for risk stratification.